(untitled) - Tchobanoglous, George (New York, 1991)
The book offers the knowledge of the environmental effects of wastewater discharges; reflects the impact of changing federal legislation on water quality control and sludge management; provides information on other types of wastewater systems, such as small systems and overflows from combined sewers
Các quá trình hóa lý trong kỹ thuật môi trường,TT. Kỹ thuật xử lý nước thải,TT. Kỹ thuật xử lý nước thải
Keywords: Sewerage,Sewerage disposal,Water reuse